Power analysis of the lower extremity during elite and sub-elite sprinting - Maraj, B.; Kivi, D.; Gervais, P. (2003)
Similar power patterns were seen between elite and non-elite sprinters. At the hip, an initial negative burst was seen after toe-off to slow down the backwards rotation of the thigh, which was followed by a positive phase to drive the thigh forwards and upwards during recovery. This was followed by another negative contraction during which the hip extensors acted eccentrically to slow down the forward rotation of the thigh. Finally, a positive contribution was seen as the sprinter initiated the backwards rotation of the thigh prior to ground contact. At the knee, an initial negative power burst was seen after toe-off, which represented the knee extensors eccentrically contracting to slow down knee flexion. This was followed by a small positive action during recovery where the knee extensors worked concentrically. Finally, the knee flexors worked eccentrically to slow down knee extension, resulting in a negative burst late in the recovery phase. The elite sprinters showed greater power output at both the hip and knee joints compared to the non-elite sprinters. Differences were most notable at the hip joint where the elite sprinters showed greater power values, particularly in concentric hip flexion. This demonstrates the importance of the hip flexors in driving the recovery leg forwards to successful sprinting. Differences at the knee were not as significant between groups, particularly in positive power output, which shows a relative unimportance of the concentric actions of the knee musculature during sprinting.